3D supramolecular chiral crystal structures of radical anion salts of (−)-NDI-Δ and possible magnetic phase diagrams. Issue 29 (16th June 2021) - Mizuno, Asato; Shuku, Yoshiaki; Suizu, Rie; Tsuchiizu, Masahisa; Awaga, Kunio
Abstract : Supramolecular chiral crystals of radical anion salts of a triangular chiral electron acceptor, (−)-naphthalene diimide (NDI)-Δ, were electrochemically grown in propylene carbonate electrolyte solutions in the presence of cyclic multidentate ligands. Abstract : Supramolecular chiral crystals of radical anion salts of a rigid triangular chiral electron acceptor, (−)-naphthalene diimide (NDI)-Δ, were electrochemically grown in propylene carbonate (PC) solutions of electrolytes (M·ClO4, M = K, Rb, Cs) in the presence of cyclic multidentate ligands, such as 18-crown-6, 15-crown-5, and 2, 2, 2-cryptand. The crystal structures were found to be formed by three-way branched π–π interactions between (−)-NDI-Δ radical anions, including [Rb(or K)(18-crown-6)] + complexes. The theoretical calculations on this structure revealed a possible magnetic phase diagram, which was governed by the ratio between two types of antiferromagnetic interactions.